2018
DOI: 10.1186/s12889-018-5836-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of HIV-positive postpartum women and health workers involved with community-based antiretroviral therapy adherence clubs in Cape Town, South Africa

Abstract: BackgroundThe rollout of universal, lifelong treatment for all HIV-positive pregnant and breastfeeding women (“Option B+”) has rapidly increased the number of women initiating antiretroviral treatment (ART) and requiring ART care postpartum. In a pilot project in South Africa, eligible postpartum women were offered the choice of referral to the standard of care, a local primary health care clinic, or a community-based model of differentiated ART services, the adherence club (AC). ACs have typically enrolled on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…In a cohort study of 129 women with HIV viral load <1000 copies/mL for at least three months, Myer and colleagues reported favourable outcomes with adherence groups during the postpartum period [87]. The feasibility and acceptability of the approach was confirmed via in‐depth interviews with healthcare providers and patients [88]. Although encouraging, further research is needed about patient preferences and long‐term outcomes in this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort study of 129 women with HIV viral load <1000 copies/mL for at least three months, Myer and colleagues reported favourable outcomes with adherence groups during the postpartum period [87]. The feasibility and acceptability of the approach was confirmed via in‐depth interviews with healthcare providers and patients [88]. Although encouraging, further research is needed about patient preferences and long‐term outcomes in this population.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mobile health (or mHealth) technologies have been shown to improve retention and adherence across numerous studies in the general adult HIV population but studies focused on antenatal and postpartum populations have been limited. In separate trials, two‐way messaging and biweekly phone calls were associated with increased retention within the first eight to ten weeks following delivery [88,89]; however, data for longer term retention (i.e. out to 12 months postpartum) appear equivocal [90].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies addressing structural factors showed promising results with integration of postpartum care into routine care for the child or family [66] [67], mHealth reminders and cash transfers [68][69][70][71][72]. Ongoing studies will evaluate effects of mHealth strategies [73,74], reaching women with mental health challenges in pregnancy and postpartum [75,76] and adherence clubs/decentralized care [77]. Women in different contexts will require different types of support [78,79] and an adaptive trial design [80] may be an efficient way to evaluate strategies to combine intervention elements to support women to remain in care [81].…”
Section: Discussionmentioning
confidence: 99%
“…The PACER study enrolled 129 postpartum breastfeeding WLH who initiated ART during their recently completed pregnancy, who met local criteria for CAC membership [20,21,28]. Eligible women were offered a choice for postpartum ART care: Model I (as described above) or Model IIIreferral directly to a CAC with their infants receiving care at well-baby clinics.…”
Section: Parent Studiesmentioning
confidence: 99%